3D Human iPSC Blood Vessel Organoids as a Source of Flow‐Adaptive Vascular Cells for Creating a Human‐Relevant 3D‐Scaffold Based Macrovessel Model. Issue 1 (27th October 2022) - Meijer, Elana M.; Koch, Suzanne E.; van Dijk, Christian G.M.; Maas, Renee G.C.; Chrifi, Ihsan; Szymczyk, Wojciech; Besseling, Paul J.; Pomp, Lisa; Koomen, Vera J.C.H.; Buikema, Jan Willem; Bouten, Carlijn V.C.; Verhaar, Marianne C.; et al.
Abstract: 3D‐scaffold based in vitro human tissue models accelerate disease studies and screening of pharmaceutics while improving the clinical translation of findings. Here is reported the use of human induced pluripotent stem cell (hiPSC)‐derived vascular organoid cells as a new cell source for the creation of an electrospun polycaprolactone‐bisurea (PCL‐BU) 3D‐scaffold‐based, perfused human macrovessel model. A separation protocol is developed to obtain monocultures of organoid‐derived endothelial cells (ODECs) and mural cells (ODMCs) from hiPSC vascular organoids. Shear stress responses of ODECs versus HUVECs and barrier function (by trans endothelial electrical resistance) are measured. PCL‐BU scaffolds are seeded with ODECs and ODMCs, and tissue organization and flow adaptation are evaluated in a perfused bioreactor system. ODECs and ODMCs harvested from vascular organoids can be cryopreserved and expanded without loss of cell purity and proliferative capacity. ODECs are shear stress responsive and establish a functional barrier that self‐restores after the thrombin challenge. Static bioreactor culture of ODECs/ODMCs seeded scaffolds results in a biomimetic vascular bi‐layer hierarchy, which is preserved under laminar flow similar to scaffolds seeded with primary vascular cells. HiPSC‐derived vascular organoids can be used as a source of functional, flow‐adaptive vascular cells for the creation of 3D‐scaffold based human macrovascular models. Abstract : In this study, it is presented a protocol for the use of human induced pluripotent stem cell‐derived vascular organoids as a source of functional, flow‐adaptive vascular cells for the creation of perfusable 3D‐scaffold based human macrovascular models. This opens the door to personalized complex vascular disease modeling in vitro.